Life, brain and consciousness : new perceptions through targeted systems analysis - Sommerhoff, Gerd (Advances in psychology (Amsterdam, Netherlands), 1990)
The relation between mind and brain can never be understood by science until the nature of consciousness and self-consciousness is clearly perceived as specific system-properties. In this volume the author tackles this problem in a rigorous analysis which begins with the general dynamics of living systems and leads the reader step-by-step towards firm conclusions about the physical processes of consciousness and the main categories of mental events. Finally the author moves from the cognitive to the affective, and proceeds to interpret a number of uniquely human sensibilities in the light of the general biological perspective he has established.